2019
DOI: 10.4236/jwarp.2019.117052
|View full text |Cite
|
Sign up to set email alerts
|

Current Seasonal Variations in Physicochemical and Heavy Metals Parameters of Sewage Treatment Plant Effluent and Suitability for Irrigation

Abstract: The study aims to investigate the current extent of physicochemical parameters and heavy metal contamination in the effluent of the Jaganpur sewage treatment plant (STP), Dayalbagh, Agra India. Majority of the nearby farmers have access to use of STP effluent in irrigation purposes for growing major edible crops. The problems of using STP effluent for irrigation purpose, continuous water quality analysis required. To check the quality of irrigation water, substantial physicochemical parameters accordance to In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…These values are higher than those reported in literature [22], for which Cu < 0.006 ppm; Pb is 0.007 and Zn < 0.00. In addition, our results are lower than the results [35] whose metal concentrations are slightly higher than the effluents of the wastewater treatment plants of Jaganpur and are respectively Pb, 1480 ppb; Zn, 1159 ppb; Cd, 119 ppb; Co, 163 ppb and Cr 123 ppb whereby it was also observed that the concentrations of Cu, Zn and Cd were below the detection limit. The values in Table 4 describe the interaction, during 4 days, between the fish and its polluted environment in the aquariums.…”
Section: Inorganic Micropollutantscontrasting
confidence: 89%
“…These values are higher than those reported in literature [22], for which Cu < 0.006 ppm; Pb is 0.007 and Zn < 0.00. In addition, our results are lower than the results [35] whose metal concentrations are slightly higher than the effluents of the wastewater treatment plants of Jaganpur and are respectively Pb, 1480 ppb; Zn, 1159 ppb; Cd, 119 ppb; Co, 163 ppb and Cr 123 ppb whereby it was also observed that the concentrations of Cu, Zn and Cd were below the detection limit. The values in Table 4 describe the interaction, during 4 days, between the fish and its polluted environment in the aquariums.…”
Section: Inorganic Micropollutantscontrasting
confidence: 89%
“…Wastes entering these water bodies are usually in both solid and liquid forms and contain elevated amounts of both inorganic and organic chemicals and their byproducts, which are often disposed of in unlined channels and streams. As a result, water bodies, which are major receptacles of treated and untreated or partially treated industrial waste, have become highly polluted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Weights ( i W ) between 0 and 1 were allocated for individual metals and the hazardous contamination index is 100 in this indexing. [48][49][50][51]40,47 The ranking is built on individual quality concerns, the relative importance of parameters and delineated as inversely proportional to the recommended standards ( i S ) for the individual parameter. First of all, the HPI computation requires the calculation of weightage ( i W ) of th i parameter employing the equation below:…”
Section: Heavy Metal Pollution Indexmentioning
confidence: 99%